Three-dimensional double friction pendulum bearing model including uplift and impact behavior: Formulation and numerical example. (15th November 2019) - Bao, Yu; Becker, Tracy
Highlights: Presents a fully three-dimensional formulation of double friction pendulum bearing. The proposed model can consider potential uplift and impact behavior in isolation bearing. Provides numerical examples to validate this model. Abstract: Friction pendulum bearings have attracted significant attention as a system to achieve multiple performance objectives under increased levels of earthquakes. Despite the tremendous progress made to develop numerical models to understand the mechanical behavior, the majority of these models still concentrate on planar behavior. Existing three-dimensional models of friction pendulum bearings usually ignore the azimuth angle of the bearing, therefore torsional resistance cannot be modeled. Moreover, important behavior such as uplift and impact cannot be included in the existing three-dimensional models. Motivated from these limitations and using double friction pendulum bearings as an example, this paper presents a three-dimensional formulation of isolation bearings which incorporates the uplift and impact behavior. Several examples are also provided to validate the proposed numerical model. The model developed in this paper will facilitate in investigations of extreme behavior of friction pendulum bearing systems or performance of these systems in buildings with novel geometries which may cause uneven displacement demands across the isolation layer.